Effects of thickness coating on the electrochemical behaviour of thermal spray Cr3C2-NiCr coatings - Guilemany, J. M.; Fernandez, J.; Delgado, J.; Benedetti, Assis Vicente [UNESP]; Climent, F. (Elsevier B.V., 2002)
Thermally sprayed HVOF coatings are increasingly being used in industrial applications where high wear and corrosion resistance are needed [1,2]. In this paper, electrochemical ac and de experiments were used in order to obtain the corrosion resistance of coated steel with different numbers of Cr3C2-NiCr layers. This work has been performed in order to determine the role of coating thickness in the corrosion behaviour of a steel protected with cermet thermally sprayed coatings. It is known that a thicker layer protects better against corrosion when a metallic coating is evaluated. But cermet coatings, such as Cr3C2-NiCr, contain higher levels of porosity and residual stresses than metallic coatings, which really could influence the corrosion resistance of the deposited layer. Electrochemical measurements, such as Open-Circuit Potential (E-Osubset of), Polarisation Resistance (RP) and Cyclic Voltammetry (CV), were performed in an aerated 3.4 NaCI media (%wt.). Electrochemical Impedance Measurements (EIS) were also done in order to obtain a mechanism that explains the corrosion process. Structural Characterisation was carried out by means of Optical and Scanning Electron Microscopes (OM, SEM) with an Energy Dispersive Spectrometry analyser (EDS). Results show that the corrosion resistance of the complete system is mainly influenced by the substrate behaviour. The application of a higher number of deposited layers did not substantially increase their anticorrosive properties. Stress generation during the spraying deposition process plays an important role in the behaviour of the coated steel against corrosion phenomena. (C) 2002 Elsevier B.V. B.V All rights reserved.
Keywords: thermal spraying; high velocity oxyfuel; cermets and composites; corrosion; impedance spectroscopy; scanning electron microscopy (SEM)